Non-aqueous electrolyte secondary battery

CN116490990BActive Publication Date: 2026-10-09PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180078536.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-11-30
Publication Date
2026-10-09
Estimated Expiration
2041-11-30

AI Technical Summary

Benefits of technology

[0014] The non-aqueous electrolyte secondary battery of the present invention has excellent charge-discharge cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116490990B_ABST
    Figure CN116490990B_ABST
Patent Text Reader

Abstract

A nonaqueous electrolyte secondary battery as one embodiment includes a positive electrode having a positive electrode mixture layer, a negative electrode, and a nonaqueous electrolyte. The positive electrode mixture layer contains a first lithium transition metal composite oxide represented by the general formula Li x Ni 1‑y‑z Co y M z O2 (in formula, 0.8 ≤ x ≤ 1.2, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.5, and M is at least one kind of metal element other than Li, Ni, and Co) and a second lithium transition metal composite oxide represented by the general formula Li a Ni 2‑a‑b Me b O2 (in formula, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a non-aqueous electrolyte secondary battery. Background Technology

[0002] Non-aqueous electrolyte secondary batteries comprise a positive electrode, a negative electrode, a separator sandwiched between the positive and negative electrodes, and a non-aqueous electrolyte, and have a structure that houses these components in an external casing. The composition of the positive electrode, a key component of non-aqueous electrolyte secondary batteries, significantly impacts battery characteristics, including charge-discharge cycle performance; therefore, much research has been conducted on the positive electrode. For example, Patent Documents 1 and 2 disclose a positive electrode active material intended to improve performance such as charge-discharge cycle characteristics.

[0003] The positive electrode active material disclosed in Patent Document 1 is of the general formula Li x Ni 1-y-z-v-w Co y Al z M1 V M2 w The composite oxide represented by O2 has element M1 selected from at least one of Mn, Ti, Y, Nb, Mo and W, and element M2 selected from at least two of Mg, Ca, Sr, Ba and Ra, and element M2 contains at least Mg and Ca.

[0004] Furthermore, the positive electrode active material disclosed in Patent Document 2 is [L]. 3a [M] 3b [O2] 6c The composite oxides shown as (L=Li, M=Ni, Mn and Co, or Li, Ni, Mn and Co) contain 0.1 to 5 mol% of one or more elements selected from Mo, W, Nb, Ta and Re relative to the total molar amount of Mn, Ni and Co.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent No. 4781004

[0008] Patent Document 2: Japanese Patent No. 5359140 Summary of the Invention

[0009] The problem the invention aims to solve

[0010] However, with the increasing use of non-aqueous electrolyte secondary batteries in automotive and energy storage applications, there is a growing demand for higher performance, particularly improved charge-discharge cycle characteristics. Existing technologies, including those in Patent Documents 1 and 2, still offer room for improvement in enhancing cycle characteristics.

[0011] Means for Solving the Problem

[0012] The non-aqueous electrolyte secondary battery of the present invention comprises: a positive electrode having a positive electrode mixture layer, a negative electrode, and a non-aqueous electrolyte, characterized in that the positive electrode mixture layer contains a compound of the general formula Li x Ni 1-y-z Co y M z O₂, wherein 0.8≤x≤1.2, 0≤y≤0.2, 0<z≤0.5, and M is at least one metal element other than Li, Ni and Co; a first lithium-transition metal composite oxide represented by the general formula Li a Ni 2-a-b Me b O₂, wherein 0<a≤0.5, 0≤b≤0.5, and Me is at least one metal element other than Li and Ni; the non-aqueous electrolyte contains a sulfonylimide salt.

[0013] Effect of the Invention

[0014] The non-aqueous electrolyte secondary battery of the present invention has excellent charge-discharge cycle characteristics. Brief Description of the Drawings

[0015] Figure 1 is a cross-sectional view of a non-aqueous electrolyte secondary battery which is an example of an embodiment.

[0016] Figure 2 is an enlarged view showing a part of a cross-section of an electrode body which is an example of an embodiment. Detailed Description of Embodiments

[0017] As described above, improving charge-discharge cycle characteristics is an important issue in non-aqueous electrolyte secondary batteries. In particular, it is desired to achieve both high capacity of the battery and good cycle characteristics. The inventors of the present invention have conducted intensive studies on improving cycle characteristics, and as a result, have found that by using a positive electrode comprising the first lithium-transition metal composite oxide represented by the general formula Li x Ni 1-y-z Co y M z O₂, and the second lithium-transition metal composite oxide represented by the general formula Li a Ni 2-a-b Me b O₂, and a non-aqueous electrolyte containing a sulfonylimide salt, the cycle characteristics of the battery are specifically improved.

[0018] The mechanism by which the combined use of a first lithium transition metal composite oxide, a second lithium transition metal composite oxide, and a sulfonyl imide salt improves cycle performance is unclear. However, it is believed that the second lithium transition metal composite oxide protects the surface of the first lithium transition metal composite oxide, thereby inhibiting degradation. Furthermore, it is thought that by adding a sulfonyl imide salt to the non-aqueous electrolyte, a high-quality protective coating is formed on the particle surface of the positive electrode active material, suppressing electrolyte side reactions on the particle surface, and thus significantly improving cycle performance.

[0019] Furthermore, the first lithium transition metal composite oxide requires Ni as an essential component, and by increasing the Ni content, it is easy to achieve both high capacity and good cycling characteristics. The effect of adding the second lithium transition metal composite oxide is even more effective when using the first lithium transition metal composite oxide with a higher Ni content.

[0020] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the various embodiments and modifications described below are selectively combined and also included in the present invention.

[0021] In the following example, a cylindrical battery is shown in which a wound electrode body 14 is housed in a bottomed cylindrical outer casing 16. However, the outer casing of the battery is not limited to a cylindrical outer casing. For example, it can be a square outer casing (square battery), a coin-shaped outer casing (coin-shaped battery), or an outer casing composed of a laminate containing a metal layer and a resin layer (laminated battery). In addition, the electrode body can also be a laminated electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators.

[0022] Figure 1 A cross-sectional view of a non-aqueous electrolyte secondary battery 10, as an example of an embodiment, is shown schematically. Figure 1 As shown, the non-aqueous electrolyte secondary battery 10 includes a wound electrode body 14, a non-aqueous electrolyte, an outer container 16 for housing the electrode body 14, and an outer container 16 for housing the non-aqueous electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound into a spiral shape with the separator 13 in between. The outer container 16 is a bottomed cylindrical metal container with an opening on one axial side, and the opening of the outer container 16 is blocked by a sealing body 17. For ease of explanation, the side with the sealing body 17 of the battery is shown as the top, and the bottom side of the outer container 16 is shown as the bottom.

[0023] The positive electrode 11, negative electrode 12, and spacer 13 constituting the electrode body 14 are all strip-shaped elongated bodies, which are alternately stacked radially in the electrode body 14 by being wound into a vortex shape. To prevent lithium deposition, the negative electrode 12 is formed to be one size larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the long side direction and the width direction (short side direction). The spacer 13 is formed to be at least one size larger than the positive electrode 11, and two sheets are arranged to clamp the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0024] Insulating plates 18 and 19 are respectively disposed above and below the electrode body 14. Figure 1 In the example shown, the positive lead 20 extends towards the sealing body 17 through the through hole in the insulating plate 18, and the negative lead 21 extends towards the bottom of the outer can 16 through the outer side of the insulating plate 19. The positive lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate, i.e., the cover 27, of the sealing body 17, which is electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative lead 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 becomes the negative terminal.

[0025] As described above, the outer can 16 is a bottomed cylindrical metal container with an opening on one axial side. A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness of the battery interior and the insulation between the outer can 16 and the sealing body 17. A groove 22 is formed on the outer can 16, protruding inward from a portion of its side portion to support the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumference of the outer can 16, with its upper surface supporting the sealing body 17. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove 22 and the open end of the outer can 16 riveted to the sealing body 17.

[0026] The sealing body 17 has a structure consisting of an inner terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 17 has, for example, a circular or ring shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the battery malfunctions and the internal pressure rises, the lower valve body 24 deforms and ruptures by pressing the upper valve body 26 towards the cover 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 ruptures, and gas is released from the opening of the cover 27.

[0027] The following is for reference only. Figure 2The positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte constituting the non-aqueous electrolyte secondary battery 10 will be described in detail below. Figure 2 It is a schematic diagram showing an enlarged part of the cross-section of the electrode body 14.

[0028] <Positive electrode>

[0029] As Figure 2 shown, the positive electrode 11 includes a positive electrode core 30 and a positive electrode mixture layer 31 formed on at least one surface of the positive electrode core 30. For the positive electrode core 30, a foil of a metal stable within the potential range of the positive electrode 11 such as aluminum or an aluminum alloy, or a thin film having the metal disposed on the surface layer can be used. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably formed on both surfaces of the positive electrode core 30. A lithium transition metal composite oxide can be used as the positive electrode active material. The positive electrode 11 can be manufactured by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, a binder, and the like onto the positive electrode core 30, drying the coating film, then compressing it, and forming the positive electrode mixture layer 31 on both surfaces of the positive electrode core 30.

[0030] Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resins, and polyolefins. In addition, these resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or salts thereof, and polyethylene oxide (PEO). Based on the total mass of the positive electrode mixture layer 31, the content of the binder is, for example, 0.1 to 5 mass%, or 0.5 to 3 mass%.

[0031] The positive electrode mixture layer 31 contains at least two types of lithium transition metal composite oxides. The first lithium transition metal composite oxide (hereinafter referred to as "composite oxide (A)") is represented by the general formula Li x Ni 1-y-z Co y M z O₂, wherein 0.8≤x≤1.2, 0≤y≤0.2, 0<z≤0.5, and M is at least one metal element other than Li, Ni, and Co. The second lithium transition metal composite oxide (hereinafter referred to as "composite oxide (B)") is represented by the general formula Li a Ni 2-a-b Me b O₂, wherein 0<a≤0.5, 0≤b≤0.5, and Me is at least one metal element other than Li and Ni.

[0032] In the positive electrode compound layer 31, the charge-discharge cycle characteristics are specifically improved by the coexistence of composite oxides (A, B). It is believed that composite oxide (B) protects the particle surface of composite oxide (A) and effectively inhibits the degradation of the particle surface, thereby significantly improving the cycle characteristics. In particular, this protective effect is believed to be more effective when the particles of composite oxides (A, B) are in contact with each other or in contact with each other through carbon nanotubes (CNTs). Furthermore, composite oxide (B) can be subjected to strong shear force and compressive force and mixed with composite oxide (A) to immobilize it on the surface of composite oxide (A).

[0033] The above-mentioned effects are achieved by adding a small amount of composite oxide (B), but in order to maintain high battery capacity and improve cycle characteristics, there is a preferred range for the amount of composite oxide (B) added. The content of composite oxide (B) relative to the total mass of the positive electrode additive layer 31 is preferably 0.05 to 10% by mass, more preferably 0.1 to 7% by mass, or 0.1 to 5% by mass. Similarly, relative to the total mass of the positive electrode active material, it is preferably 0.05 to 10% by mass, more preferably 0.1 to 7% by mass, or 0.1 to 5% by mass. When the amount of composite oxide (B) is within this range, the cycle characteristics can be effectively improved.

[0034] The positive electrode additive layer 31 may contain composite oxides other than composite oxides (A, B) (e.g., lithium transition metal composite oxides that do not satisfy the above general formula) without prejudice to the purpose of the present invention. The composite oxides (A, B) preferably contain 50% by mass or more relative to the total mass of the positive electrode additive layer 31. The total content of the composite oxides (A, B) relative to the total mass of the positive electrode additive layer 31 is, for example, 85% by mass or more, or 90% by mass or more, or 95% by mass or more. An example of a suitable content is 90-99% by mass, or 95-99% by mass.

[0035] [First Lithium Transition Metal Composite Oxide (Composite Oxide (A))]

[0036] The composite oxide (A) is a composite oxide represented by the above general formula, and contains at least one metallic element M other than Li, Ni, and Co as an essential constituent element. Furthermore, the composite oxide (A) preferably contains Co. However, Co is particularly rare and has a high valence, so the composite oxide (A) may substantially not contain Co. When the composite oxide (A) contains Co, the content of Co relative to the total molar amount of metallic elements other than Li is 20 mol% or less, more preferably 0.1 to 10 mol%, or 0.5 to 5 mol%. It should be noted that the molar fraction of the metallic element in the composite oxide can be determined by inductively coupled plasma (ICP) luminescence spectrophotometry.

[0037] For the composite oxide (A), Ni is preferably the most abundant among the metal elements other than Li. The Ni content is preferably 50 mol% or more, more preferably 70 mol% or more, and particularly preferably 80 mol% or more, relative to the total molar amount of the metal elements other than Li. Suitable examples of Ni content are 80–97 mol%, or 85–95 mol%. That is, suitable examples of (1-yz) representing Ni content in the above general formula are 0.80 ≤ (1-yz) ≤ 0.97, or 0.85 ≤ (1-yz) ≤ 0.95.

[0038] As described above, a suitable example of a composite oxide (A) is a composite oxide containing 80 mol% or more Ni relative to the total molar amount of metal elements other than Li. By increasing the proportion of Ni among the metal elements in the composite oxide (A), higher battery capacity can be achieved. Furthermore, the combination of Ni-rich composite oxide (A) and composite oxide (B) is effective in improving cycle characteristics. In the above general formula, x, representing the Li content, is 0.8 ≤ x ≤ 1.2 or 0.97 ≤ x ≤ 1.2, and the composite oxide (A) can be a lithium-excess type composite oxide where the molar ratio of Li to the transition metal exceeds 1.

[0039] The composite oxide (A) contains at least one metallic element M other than Li, Ni, and Co. The metallic element M is, for example, selected from at least one of Mn, W, Mg, Mo, Nb, Ti, Si, Al, Zr, B, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, and Ca, more preferably selected from at least one of Mn, W, Mg, Mo, Nb, Ti, Si, Sr, Ca, and Al. Preferably, it contains at least one of Mn and Al. The content of metallic element M, when multiple elements are present, is total, and relative to the total molar amount of metallic elements other than Li, is 50 mol% or less, more preferably 0.1–20 mol%, or 0.5–10 mol%, or 1–5 mol%.

[0040] The composite oxide (A) has, for example, a crystal structure belonging to space group R3-m. Furthermore, the composite oxide (A) has a layered structure comprising a transition metal layer, a Li layer, and an oxygen layer. In this case, the protective effect of the composite oxide (B) is more effective, maintaining a stable crystal structure even under repeated charge-discharge cycles, thus improving cycle characteristics more effectively. In addition, the BET specific surface area of ​​the composite oxide (A) is, for example, 0.2–2.0 m². 2 / g. BET specific surface area was determined according to the BET method (nitrogen adsorption method) as described in JIS R1626.

[0041] The composite oxide (A) is, for example, a secondary particle composed of aggregates of multiple primary particles. An example of the median particle size (D50) of the composite oxide (A) on a volume basis is 3–20 μm, or 5–15 μm. D50 refers to the particle size at which the frequency accumulates to 50% from the smallest particle size in the volumetric particle size distribution; it is also called the median diameter. The particle size distribution of the secondary particles of the composite oxide can be determined using a laser diffraction particle size distribution measuring device (e.g., MicrotracBEL MT3000II) with water as the dispersion medium. The particle size of the primary particles of the composite oxide (A) is, for example, 0.05 μm–1 μm. The particle size of the primary particles is determined as the diameter of the circumcircle in a cross-sectional image of the secondary particles observed by a scanning electron microscope (SEM).

[0042] Furthermore, a compound containing at least one of Sr, Ca, W, Mg, Nb, and Al (hereinafter referred to as "metal element M2") can be immobilized on the surface of the composite oxide (A) particles. The M2 compound containing metal element M2 can exist in a dotted manner on the surface of the composite oxide (A) particles, or it can exist in a layered manner covering the entire particle surface. The thickness of the M2 compound layer is, for example, 0.1–5 nm. It is believed that the M2 compound protects the surface of the composite oxide (A), or also the surface of the composite oxide (B), thereby suppressing electrolyte side reactions on the surface of the composite oxide (A, B) particles.

[0043] The M2 compound is an oxide, hydroxide, or carbonate. Specific examples of M2 compounds include SrO, CaO, Sr(OH)2, Ca(OH)2, SrCO3, and CaCO3. The amount of the M2 compound, relative to the total molar number of the metal elements other than Li constituting the complex oxide (A), is, for example, 0.05–0.5 mol% when converted to the metal element M2. The presence of the M2 compound can be confirmed by energy-dispersive X-ray spectroscopy (TEM-EDX). Furthermore, the metal element M2 can be determined by ICP-N spectroscopy analysis of a solution obtained by dissolving the complex oxide (A) in fluorinated nitric acid.

[0044] The composite oxide (A) is manufactured, for example, through the following steps: Step 1, in which a composite oxide containing Ni, metal element M, etc., is obtained; Step 2, in which the composite oxide is mixed with Li raw material to obtain a mixture; Step 3, in which the mixture is calcined. If the M2 compound is fixed on the particle surface of the composite oxide (A), a raw material containing metal element M2 (hereinafter referred to as "M2 raw material") can be added in Step 2. The composition, particle size, BET specific surface area, etc., of the composite oxide (A) and the M2 compound can be adjusted by controlling the mixing ratio of the raw material and the calcination conditions in Step 3.

[0045] In the first step, for example, while stirring a solution containing a metal salt of a metal element such as Ni and metal element M, an alkaline solution such as sodium hydroxide is added dropwise to adjust the pH towards the alkaline side (e.g., 8.5–12.5), thereby causing the metal-containing complex hydroxide to precipitate (co-precipitate). Then, by calcining this complex hydroxide, a complex oxide containing Ni, metal element M, etc., is obtained. There are no particular limitations on the calcination temperature, but as an example, it is 300–600°C.

[0046] In the second step, a mixture is obtained by mixing the composite oxide obtained in the first step, the Li raw material, and the required M2 raw material. Examples of Li raw materials include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of M2 raw materials include oxides, hydroxides, carbonates, nitrates, and sulfates of M2. The mixing ratio of the composite oxide obtained in the first step to the Li raw material is adjusted, for example, by a molar ratio of metal elements other than Li to Li of 1:0.98 to 1:1.22. Furthermore, the mixing ratio of the composite oxide to the M2 raw material is adjusted, for example, by a molar ratio of metal elements other than Li to M2 of 1:0.0005 to 1:0.005.

[0047] In the third step, the mixture obtained in the second step is fired at a specified temperature and time to obtain a fired product. The firing of the mixture is performed, for example, through a multi-stage firing process including the following steps: a first firing step, in a firing furnace, under an oxygen flow, firing at a first heating rate to a first set temperature of 450°C or higher and 680°C or lower; a second firing step, after the first firing step, in a firing furnace, under an oxygen flow, firing at a second heating rate to a second set temperature exceeding 680°C and below 800°C. The first heating rate is 1.5 to 5.5°C / min, and the second heating rate is slower than the first heating rate, and can be 0.1 to 3.5°C / min. It should be noted that multiple heating rates can be set in each firing step.

[0048] The holding time of the first set temperature in the first firing process is, for example, 0 to 5 hours, or 0 to 3 hours. It should be noted that the holding time of the set temperature refers to the time during which the set temperature is maintained after it has been reached. The holding time of the second set temperature in the second firing process is, for example, 1 to 10 hours, or 1 to 5 hours. The firing of the mixture is carried out in an oxygen flow with an oxygen concentration of 60% or higher. The flow rate of the oxygen flow can be expressed as per 10 cm³ of the firing furnace. 3 The flow rate is 0.2–4 mL / min, and for mixtures, it is 0.3 L / min or higher per 1 kg. For calcined products, impurities can be removed by washing with water, dehydration, and drying.

[0049] It should be noted that the M2 raw material may not be added in the second step, but added in the third step, when washing the fired product with water, or during drying. For example, heat treatment is performed at 150 to 400°C for 0.5 to 15 hours in a vacuum atmosphere, thereby fixing the M2 compound on the particle surface of the composite oxide (A).

[0050] [Second lithium-transition metal composite oxide (Composite Oxide (B))]

[0051] As described above, the composite oxide (B) is represented by the general formula Li a Ni 2-a-b Me b O₂, wherein 0<a≤0.5, 0≤b≤0.5, and Me is at least one metal element other than Li and Ni. The content of the metal element Me is preferably less than the contents of Li and Ni, for example, less than 10 mol% or less than 5 mol% relative to the total molar amount of metal elements. As an example of the metal element Me, at least one selected from the group consisting of Cu, Sr, Ca, Nb, Si and Al can be mentioned.

[0052] For the composite oxide (B), the release and absorption of Li during charge and discharge do not occur, and the composition thereof does not change. When such composite oxide (B) is used in combination with composite oxide (A), the cycle characteristics of the battery are specifically improved. The composite oxide (B) may contain a plurality of composite oxides with similar compositions. In the above general formula, a is more preferably 0.1≤a≤0.5, or 0.2≤a≤0.4. When a is within this range, the cycle characteristics are more effectively improved. It should be noted that the composition of the composite oxide (B) can be identified by X-ray diffraction pattern and analyzed by ICP emission spectrometry.

[0053] Composite oxide (B) is, for example, a composite oxide having at least one diffraction peak with a peak top at a diffraction angle (2θ) of 21.40° to 21.65° in synchrotron radiation X-ray diffraction (photon energy 16 keV). The diffraction peak only needs to have a peak top in the range of 2θ=21.40° to 21.65°, and may also be a broad peak where the entire peak does not exist within this range. In the X-ray diffraction pattern of composite oxide (B), for example, there is one peak top in the range of 2θ=21.40° to 21.65°.

[0054] The X-ray diffraction pattern of composite oxide (B) is obtained by powder X-ray diffraction method under the following conditions using a synchrotron radiation facility (optical path BL5S2 of Aichi Synchrotron Radiation Center).

[0055] Photon energy: 16 keV

[0056] Scanning range: 10–90°

[0057] Analytical optical system: Debye-Scherrer type

[0058] The obtained data were analyzed using the identification software PDXL (made by Rigaku Corporation) to identify peaks and composite oxides (B).

[0059] In measurements performed using the aforementioned apparatus, NiO exhibited a peak at 21.36°, which shifted towards higher angles as the value of 'a' in the aforementioned formula increased. When 'a' in the aforementioned formula was within the aforementioned range, a main peak was observed at 21.40° to 21.65°. The composite oxide (B) could be identified by comparison with a JCPDS card containing other peaks.

[0060] The composite oxide (B) is, for example, a secondary particle with a smaller particle size than the composite oxide (A), formed by the aggregation of multiple primary particles. An example of the D50 of the composite oxide (B) is 1–15 μm, 1–10 μm, or 2–7 μm. The D50 of the composite oxide (B) can be less than half of the D50 of the composite oxide (A), preferably 1 / 5 to 1 / 2, or 1 / 3 to 1 / 2, of the D50 of the composite oxide (A). By making the particle size of the composite oxide (B) smaller than that of the composite oxide (A), good contact between the particles can be obtained, improving the cycling performance. Furthermore, the BET specific surface area of ​​the composite oxide (B) is, for example, 0.5–2.5 m². 2 / g.

[0061] The composite oxide (B) exists in the cathode compound layer 31, for example, surrounded by multiple composite oxides (A). Furthermore, the particle surfaces of the composite oxides (A, B) are in contact with each other. In this case, it is believed that the interaction between the composite oxides (A, B) is more effectively manifested, improving the cycle performance. It should be noted that the composite oxide (B) is not limited to an intentionally added substance; it can be incorporated as a byproduct of the composite oxide (A) or as an impurity in other cathode materials.

[0062] The composite oxide (B) is manufactured, for example, via the following steps: a first step of mixing a specified amount of Li raw material and Ni raw material to obtain a mixture; and a second step of calcining the mixture at 500–800°C for 10–30 hours. In the first step, the raw materials may be pulverized as needed, or a raw material containing the metallic element Me may be added within the range where the X-ray diffraction pattern of the composite oxide (B) satisfies the above conditions. Furthermore, in the second step, the mixture may be granulated and then calcined, or it may be crushed after calcination. The calcination in the second step may be carried out, for example, in the atmosphere or in an oxygen atmosphere.

[0063] As an example of the Li raw material, there can be mentioned Li₂CO₃, LiOH, Li₂O₂, Li₂O, LiNO₃, LiNO₂, Li₂SO₄, LiOH·H₂O, LiH, LiF, etc. As an example of the Ni raw material, there can be mentioned NiO, Ni(OH)₂, NiCO₃, NiSO₄, Ni(NO₃)₂, etc. The mixing ratio of the Li raw material and the Ni raw material is adjusted, for example, in such a manner that the X-ray diffraction pattern of the composite oxide (B) satisfies the above conditions, and a in the above general formula satisfies the condition of 0 < a ≤ 0.5.

[0064] [Conductive agent]

[0065] As described above, the positive electrode mixture layer 31 contains a conductive agent. The conductive agent forms a good conductive path in the positive electrode mixture layer 31 and contributes to reducing the resistance of the positive electrode mixture layer 31. In the positive electrode mixture layer 31, carbon nanotubes (CNT) are contained as a conductive agent. In addition, the positive electrode mixture layer 31 can simultaneously contain CNT and granular conductive agents such as carbon black, acetylene black, Ketjen black, and graphite, fibrous conductive agents such as vapor grown carbon fiber (VGCF), electrospun carbon fiber, polyacrylonitrile (PAN)-based carbon fiber, pitch-based carbon fiber, and graphene-based conductive agents.

[0066] It is considered that CNT forms a good conductive path in the positive electrode mixture layer 31, connects the particles of the composite oxides (A, B) to each other, and improves the surface protection effect provided by the composite oxide (B). By coexisting the composite oxide (B) and CNT, the cycle characteristics of the battery are specifically improved. Relative to the total mass of the positive electrode mixture layer 31, the content of CNT is, for example, 0.01 to 5 mass%, more preferably 0.04 to 2 mass%, or 0.06 to 0.8 mass%. When the content of CNT is within this range, the cycle characteristics can be effectively improved. The positive electrode mixture layer 31 may contain only CNT as the conductive agent.

[0067] CNT can be any of single-walled CNT (SWCNT) and multi-walled CNT (MWCNT). In addition, as MWCNT, for example, there can be used CNT with a tubular membrane structure in which graphene sheets formed by six-membered carbon rings are卷曲 parallel to the fiber axis, CNT with a sheet structure in which graphene sheets formed by six-membered carbon rings are arranged perpendicular to the fiber axis, and CNT with a herringbone structure in which graphene sheets formed by six-membered carbon rings are卷曲 at an oblique angle relative to the fiber axis. Two or more types of CNT can also be added to the positive electrode mixture layer 31.

[0068] The average diameter of CNTs is, for example, 50 nm or less, preferably 40 nm or less, more preferably 25 nm or less, or 20 nm or less. The lower limit of the average diameter of CNTs is not particularly limited; for example, it is 1 nm or 5 nm. A suitable range for the average diameter of CNTs is 1–20 nm, or 5–20 nm. When the average diameter of CNTs is within this range, the improvement in cycle performance is enhanced compared to using CNTs with an average diameter outside this range.

[0069] The average fiber length of CNTs is, for example, 0.5 μm or more, preferably 0.7 μm or more, more preferably 0.8 μm or more, or 1 μm or more. There is no particular upper limit to the average fiber length of CNTs, but as an example, it is 10 μm or 5 μm. An example suitable range for the average fiber length of CNTs is 1 to 10 μm, or 1 to 5 μm. When the average fiber length of CNTs is within this range, the improvement in cycle characteristics is enhanced compared to using CNTs with an average fiber length outside this range.

[0070] The average fiber length of CNTs is, for example, shorter than that of composite oxide (B)D50. It should be noted that the average diameter of CNTs is obtained by averaging the measurements of 100 CNTs selected from the surface TEM image of the positive electrode compound layer 31 and the average fiber length is obtained from the cross-sectional SEM image of the positive electrode compound layer 31.

[0071] <Negative electrode>

[0072] like Figure 2 As shown, the negative electrode 12 has a negative electrode core 40 and a negative electrode binder layer 41 formed on at least one surface of the negative electrode core 40. For the negative electrode core 40, a foil of a metal stable within the potential range of the negative electrode, such as copper or a copper alloy, or a thin film with that metal disposed on the surface can be used. The negative electrode binder layer 41 contains a negative electrode active material and a binder, and it is preferable that it is formed on both surfaces of the negative electrode core 40. Furthermore, a conductive agent such as CNT can be added to the negative electrode binder layer 41. The negative electrode 12 can be manufactured by coating a negative electrode binder slurry containing a negative electrode active material and a binder onto the negative electrode core 40, drying the coating, and then compressing it to form the negative electrode binder layer 41 on both surfaces of the negative electrode core 40.

[0073] In the negative electrode compound layer 41, the negative electrode active material includes a carbon-based active material and at least one of the following: Si, Sn, Sb, Mg, and Ge (hereinafter referred to as "metal element M3") and an M3 compound containing metal element M3. The content of metal element M3 and M3 compound relative to the total mass of the negative electrode active material is, for example, 0.5 to 30% by mass, preferably 1 to 15% by mass.

[0074] The metallic element M3 may be added to the negative electrode mixture layer 41, but it is preferable to add an M3 compound. Examples of the M3 compound include SiC, SnO₂, a first silicon material (SiO) containing a silicon oxide phase and Si dispersed in the silicon oxide phase, a second silicon material (LSX) containing a lithium silicate phase and Si dispersed in the lithium silicate phase, and a third silicon material (Si-C) containing a carbon phase and Si dispersed in the carbon phase. Among these, SiO, LSX or Si-C is preferred.

[0075] For carbon-based active materials, for example, natural graphite such as flaky graphite, and artificial graphite such as bulk artificial graphite and graphitized mesocarbon microbeads can be used. Based on the mass of the negative electrode active material, the content of the carbon-based active material (graphite) is, for example, 70 to 99.5 mass%, or 85 to 99 mass%. In addition, an example of the D50 of the carbon-based active material is 1 to 20 μm, or 2 to 15 μm. By using the carbon-based active material in combination with the M3 compound, high capacity can be achieved while maintaining good cycle characteristics.

[0076] SiO and LSX are, for example, particles whose D50 is smaller than the D50 of graphite. An example of the D50 of SiO and LSX is 1 μm to 15 μm, or 3 μm to 10 μm. A conductive layer made of a highly conductive material can be formed on the particle surfaces of SiO and LSX. An example of a suitable conductive layer is a carbon coating film made of a carbon material. Considering the ensuring of conductivity and the diffusion of lithium ions into the particles, the thickness of the conductive layer is preferably 1 to 200 nm, or 5 to 100 nm.

[0077] SiO has a particle structure in which fine Si particles are dispersed in a silicon oxide phase. Suitable SiO has a sea-island structure in which fine Si particles are substantially uniformly dispersed in an amorphous silicon oxide matrix, represented by the general formula SiO x (0 < x ≤ 2). The silicon oxide phase is composed of an aggregate of particles finer than the Si particles. From the viewpoint of achieving both battery capacity and cycle characteristics, the content of Si particles is preferably 35 to 75 mass% relative to the total mass of SiO.

[0078] The average particle diameter of Si particles dispersed in the silicon oxide phase is, for example, 500 nm or less before charge and discharge, preferably 200 nm or less, or 50 nm or less. After charge and discharge, it is, for example, 400 nm or less, or 100 nm or less. The average particle diameter of Si particles is obtained by observing the particle cross-section of SiO using SEM or transmission electron microscope (TEM), and calculating the average value of the longest diameters of 100 Si particles.

[0079] LSX has a particle structure in which fine Si particles are dispersed in a lithium silicate phase. A suitable LSX has a sea-island structure in which fine Si particles are substantially uniformly dispersed in a matrix of lithium silicate. The lithium silicate phase is composed of an aggregate of particles finer than the Si particles. As in the case of SiO, the content of Si particles relative to the total mass of LSX is preferably 35 to 75 mass%. In addition, the average particle diameter of the Si particles before charge and discharge is, for example, 500 nm or less, preferably 200 nm or less, or 50 nm or less.

[0080] The lithium silicate phase is preferably represented by the general formula Li 2z SiO (2+z) (0 < z < 2) represented compound. That is, the lithium silicate phase does not contain Li4SiO4 (Z=2). Li4SiO4 is an unstable compound that reacts with water to exhibit alkalinity, which may sometimes cause Si to deteriorate, resulting in a decrease in charge and discharge capacity. From the viewpoints of stability, ease of production, lithium ion conductivity and the like, the lithium silicate phase preferably contains Li2SiO3 (Z=1) or Li2Si2O5 (Z=1 / 2) as a main component. When Li2SiO3 or Li2Si2O5 is used as the main component, the content of the main component relative to the total mass of the lithium silicate phase is preferably more than 50 mass%, more preferably 80 mass% or more.

[0081] Si-C has a carbon phase and silicon particles dispersed in the carbon phase. From the perspective of increasing capacity and other aspects, the content of silicon particles in suitable Si-C is preferably 30 mass% or more and 80 mass% or less, more preferably 35 mass% or more and 75 mass% or less, and still more preferably 55 mass% or more and 70 mass% or less. The average particle diameter of suitable silicon particles before charging and discharging is generally 500 nm or less, preferably 200 nm or less, more preferably 100 nm or less. After charging and discharging, it is preferably 400 nm or less, more preferably 100 nm or less. The average particle diameter of the silicon particles is measured by observing the cross section of Si-C particles using SEM or TEM, and specifically, can be obtained as the average value of the longest diameters of 100 silicon particles.

[0082] For the binder contained in the negative electrode mixture layer 41, fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc. can be used in the same manner as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is particularly preferably used. In addition, the negative electrode mixture layer 41 further preferably contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like. Among these, it is suitable to use SBR in combination with CMC or a salt thereof, PAA or a salt thereof. Relative to the mass of the negative electrode active material, the content of the binder is, for example, 0.1 to 5 mass%.

[0083] <Separator>

[0084] as Figure 2As shown, the separator 13 has a porous substrate 50 and a surface layer 51 formed on the surface of the substrate 50 facing the positive electrode 11. The surface layer 51 is a layer containing inorganic particles and a binder. The surface layer 51 can be formed on both sides of the substrate 50, but from the viewpoint of high capacity, it is preferable to form it only on one side of the substrate 50 facing the positive electrode 11. The separator 13 is a porous sheet between the positive electrode 11 and the negative electrode 12, preventing electrical contact between the two electrodes, and has ion permeability and insulation. The porosity of the separator 13 is, for example, 30% to 70%. It should be noted that the porosity of the separator 13 is determined by the porosity of the substrate 50.

[0085] The substrate 50 is a porous sheet made of resin. The thickness of the substrate 50 is, for example, 5 to 50 μm, more preferably 10 to 30 μm. The resin constituting the substrate 50 is not particularly limited, but specific examples include polyolefins such as polyethylene, polypropylene, copolymers of ethylene and α-olefins, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polyetheretherketone, polyimide, fluoropolymers, and cellulose. The substrate 50 can be a single-layer structure or a laminated structure such as a three-layer structure of polyethylene / polypropylene / polyethylene.

[0086] The surface layer 51, like the substrate 50, is porous, exhibiting ion permeability and insulation. The thickness of the surface layer 51 is not particularly limited, but it is preferably thinner than the substrate 50, for example, 0.5–10 μm, more preferably 1–6 μm. It is preferable that the surface layer 51 is in contact with the surface of the positive electrode binder layer 31 and is formed over approximately the entire area of ​​one side of the substrate 50. The surface layer 51 is formed, for example, by applying a slurry containing inorganic particles and a binder to the entire surface of the substrate 50 and then allowing the coating to dry.

[0087] The surface layer 51 is a layer with inorganic particles as the main component. The content of inorganic particles relative to the total mass of the surface layer 51 is, for example, 70% by mass or more, preferably 80% by mass or more. Suitable ranges for the content of inorganic particles are 70-99% by mass, 80-98% by mass, or 85-95% by mass. The surface layer 51 has the function of suppressing damage to the separator 13 caused by conductive foreign matter and deformation of the separator 13 during abnormal heating. Furthermore, the surface layer 51, which is in contact with the positive electrode 11, can be considered to suppress side reactions of the electrolyte on the positive electrode 11 caused by interaction with the composite oxide (B). By providing the surface layer 51, the cycle characteristics and storage characteristics of the battery are specifically improved.

[0088] Examples of inorganic particles included in the surface layer 51 include metal oxides, metal nitrides, metal fluorides, metal carbides, aluminum hydroxide (boehmite), magnesium hydroxide and other metal hydroxides, calcium carbonate, magnesium carbonate, barium carbonate and other metal carbonates, calcium sulfate, magnesium sulfate, barium sulfate and other metal sulfates. One type of inorganic particle can be used alone, or two or more types can be used in combination. The D50 of the inorganic particles is, for example, 0.01–10 μm, preferably 0.05–5 μm.

[0089] Examples of metal oxides include aluminum oxide (bauxite), titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, and manganese oxide. Examples of metal nitrides include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluorides include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbides include silicon carbide, boron carbide, titanium carbide, and tungsten carbide. From the viewpoint of improving recycling and preservation characteristics, a suitable inorganic particle is selected from at least one of bauxite, boehmite, and barium sulfate.

[0090] The binder included in the surface layer 51 is not particularly limited as long as it is a material capable of fixing inorganic particles to each other and to the substrate 50, and possessing electrolyte resistance. For example, the same material used in the positive electrode binder layer 31 and the negative electrode binder layer 41 can be used. Specific examples include fluoropolymers such as PVdF and PTFE, PAN, and acrylic resins. Furthermore, resins with high heat resistance, such as aromatic amide resins, can also be used. As a suitable binder, at least one selected from aromatic amide resins and acrylic resins can be mentioned.

[0091] [Non-aqueous electrolytes]

[0092] Non-aqueous electrolytes comprise a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixtures of two or more of these. The non-aqueous solvent may contain a halogen substituent in which at least a portion of the hydrogen atoms of the solvent is replaced by a halogen atom such as fluorine. Examples of halogen substituents include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP). It should be noted that non-aqueous electrolytes are not limited to liquid electrolytes and can also be solid electrolytes.

[0093] In the non-aqueous electrolyte, a sulfonylimide salt is contained as an electrolyte salt. In a non-aqueous electrolyte secondary battery 10 including a positive electrode 11 containing a composite oxide (A, B), it is considered that adding a sulfonylimide salt to the non-aqueous electrolyte forms a good protective coating film on the particle surface of the positive electrode active material, inhibits the side reaction of the electrolyte on the particle surface, and specifically improves cycle characteristics. The concentration of the sulfonylimide salt is preferably 0.05 to 2.5 mol / L, more preferably 0.1 to 2.0 mol / L, or 0.1 to 1.5 mol / L. When the content of the sulfonylimide salt falls within this range, the cycle characteristics can be improved more effectively.

[0094] The sulfonylimide salt added to the non-aqueous electrolyte is preferably lithium sulfonylimide. Examples of lithium sulfonylimide include lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide, lithium bis(nonafluorobutanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide (LIBETI), etc. Among them, at least one lithium sulfonylimide selected from LiFSI and lithium bis(trifluoromethanesulfonyl)imide is preferred. One sulfonylimide salt may be used alone, or two or more sulfonylimide salts may be used in combination.

[0095] The non-aqueous electrolyte may further contain other lithium salts. Examples of other lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic lithium carboxylate, Li2B4O7, borates such as Li(B(C2O4)F2), etc. Among them, LiPF6 is preferably used from the viewpoints of ionic conductivity, electrochemical stability, etc.

[0096] In the non-aqueous electrolyte, it is preferable that lithium sulfonylimide and a second lithium salt coexist. In this case, a combination of LiFSI and LiPF6 is particularly preferable. When the second lithium salt is contained, the concentration of lithium sulfonylimide is also adjusted to the above range, for example. As a specific example, the concentration of lithium sulfonylimide is set to 0.1 to 1.5 mol / L, and the total concentration of lithium salts is set to 1.5 to 2.5 mol / L. The concentration of lithium sulfonylimide is, for example, 30 to 70% of the concentration of the lithium salt contained in the non-aqueous electrolyte.

[0097] In addition, non-aqueous electrolytes may contain additives such as vinylene carbonate (VC), ethylene sulfite (ES), cyclohexylbenzene (CHB), o-terphenyl (OTP), and propanesulfonic acid lactone compounds. Among these, VC is preferred for increasing capacity. The concentration of the additives is not particularly limited, but is typically 0.1% to 5% by mass.

[0098] As mentioned above, non-aqueous solvents can include esters and ethers. Examples of esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).

[0099] Examples of ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-eucalyptol, crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, and ethyl ethyl ether. Alkenyl ethers, butyl vinyl ethers, methyl phenyl ethers, ethyl phenyl ethers, butyl phenyl ethers, pentyl phenyl ethers, methoxytoluene, benzyl ethyl ethers, diphenyl ethers, dibenzyl ethers, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and other chain ethers.

[0100] (Modified Example)

[0101] On the surface of the composite oxide (A) particles, other compounds, such as those containing lanthanides, can be fixed instead of compounds containing the metal element M2. Alternatively, there may be no fixed material on the surface of the composite oxide (A) particles. Furthermore, small-particle-size composite oxides (B) can also be fixed on the surface of the composite oxide (A) particles.

[0102] The positive electrode flux layer may not contain CNTs; instead, it may contain carbon black, acetylene black, Ketjen black, graphite, etc., as a conductive agent. Furthermore, the negative electrode flux layer may not contain the metal element M3 and M3 compounds; instead, it may contain only carbon-based active materials such as graphite as the negative electrode active material.

[0103] The separator can also be a porous sheet without a surface layer mainly composed of inorganic particles. Alternatively, a surface layer mainly composed of inorganic particles can also be provided on the surface of the positive electrode mixture layer.

[0104] Example

[0105] The present invention will be further described below through embodiments, but the present invention is not limited to these embodiments.

[0106] <Example 1>

[0107] [Synthesis of composite oxide (Al)]

[0108] [Ni] obtained by coprecipitation method 0.91 Co 0.04 Al 0.05 The composite hydroxide shown in [(OH)2] was calcined at 500°C for 8 hours to obtain the composite oxide (Ni). 0.91 Co 0.04 Al 0.05 O2 (Step 1). Next, lithium hydroxide (LiOH) and the above-mentioned composite oxide are mixed in a molar ratio of Li to Ni, Co, and Al of 1.02:1 to obtain a mixture. This mixture is then subjected to an oxygen flow of 95% oxygen concentration (per 10 cm³). 3 The mixture was calcined at a flow rate of 2 mL / min and 5 L / min per kg of the mixture, from room temperature to 650°C, and then at a heating rate of 0.5°C / min, from 650°C to 720°C. The calcined product was washed with water to remove impurities, yielding the composite oxide (Al).

[0109] ICP analysis revealed that the composite oxide (Al) had a composition of LiNi. 0.91 Co 0.04 Al 0.05 O2. Furthermore, the crystal structure of the first lithium transition metal complex oxide was identified as belonging to space group R-3m by X-ray diffraction. The D50 of the complex oxide (Al) was determined to be 10 μm using an MT3000II micrometer manufactured by MicrotracBEL with water as the dispersion medium.

[0110] [Synthesis of composite oxide (B1)]

[0111] Li₂O and NiO were weighed in a Li:Ni molar ratio of 0.3:1.7, pulverized, and mixed to prepare a mixture. This mixture was then calcined at 650°C for 20 hours under an oxygen atmosphere, followed by further pulverization to obtain a composite oxide (B₁). Powder X-ray diffraction analysis of the composite oxide (B₁) using the aforementioned synchrotron radiation facility revealed a peak with a apex at 21.48° within the 2θ range of 21.40° to 21.65° of the obtained X-ray diffraction pattern. Furthermore, the composition of the composite oxide (B₁) was confirmed as Li₂O by comparison with a JCPDS card containing other peaks. 0.3 Ni 1.7 O2. The D50 of the composite oxide (B1) was 5 μm, determined using a MicrotracBEL MT3000II with water as the dispersion medium.

[0112] [The production of the positive electrode]

[0113] A mixture of composite oxides (Al, B1) in a mass ratio of 99.9:0.1 is used as the positive electrode active material. The positive electrode active material, acetylene black (AB), and polyvinylidene fluoride (PVdF) are mixed in a solid component mass ratio of 92:5:3, and an appropriate amount of N-methylpyrrolidone (NMP) is added. The mixture is then kneaded to prepare a positive electrode slurry. This positive electrode slurry is coated onto a positive electrode core made of aluminum foil. After the coating dries, it is rolled using rolling mills and cut into specified electrode sizes, resulting in a positive electrode with positive electrode slurry layers formed on both sides of the positive electrode core. It should be noted that a portion of the positive electrode has an exposed portion that exposes the surface of the positive electrode current collector.

[0114] [Making the negative electrode]

[0115] As a negative electrode active material, graphite and SiO2 are used. x (X=1.0) represents a substance formed by mixing SiO in a mass ratio of 95:5. A negative electrode active material, a styrene-butadiene rubber (SBR) dispersant, and sodium carboxymethyl cellulose (CMC-Na) are mixed in a solid component mass ratio of 98:1:1, with water used as the dispersion medium to prepare a negative electrode slurry. Next, this negative electrode slurry is coated onto both sides of a negative electrode core made of copper foil. After the coating is dried and compressed, it is cut to the specified electrode size to create a negative electrode with a negative electrode slurry layer formed on both sides of the negative electrode core.

[0116] [Preparation of non-aqueous electrolytes]

[0117] Non-aqueous electrolytes were prepared by dissolving LiFSI at a concentration of 0.5 mol / L and LiPF6 at a concentration of 1.0 mol / L in a mixed solvent consisting of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 (25°C, 1 atmosphere).

[0118] [Fabrication of the Experimental Battery Cell]

[0119] The positive electrode with an aluminum positive electrode lead and the negative electrode with a nickel negative electrode lead are wound into a spiral shape with a polyethylene separator in between, and then flattened to form a wound electrode body. The electrode body is housed in an outer casing made of aluminum laminate, and after the non-aqueous electrolyte is injected, the opening of the outer casing is sealed to produce an evaluation test battery cell.

[0120] <Example 2>

[0121] In the fabrication of the positive electrode, the composite oxides (Al, B1) were mixed at a mass ratio of 99.8:0.2. Otherwise, the test cell was fabricated in the same manner as in Example 1.

[0122] <Example 3>

[0123] In the fabrication of the positive electrode, the composite oxides (Al, B1) were mixed at a mass ratio of 99.7:0.3. Otherwise, the test cell was fabricated in the same manner as in Example 1.

[0124] <Example 4>

[0125] In the preparation of the non-aqueous electrolyte, LiFSI was dissolved at a concentration of 1.0 mol / L and LiPF6 at a concentration of 0.5 mol / L, respectively. Otherwise, the test battery cells were prepared in the same manner as in Example 2.

[0126] <Example 5>

[0127] A composite oxide (B2) was synthesized by mixing Li2O and NiO in a Li to Ni molar ratio of 0.2:1.8. Otherwise, test cell cells were fabricated in the same manner as in Example 2.

[0128] <Example 6>

[0129] A composite oxide (B3) was synthesized by mixing Li2O and NiO in a Li to Ni molar ratio of 0.5:1.5. Otherwise, test battery cells were fabricated in the same manner as in Example 2.

[0130] <Comparative Example 1>

[0131] In the fabrication of the positive electrode, composite oxide (B1) was not used. Otherwise, the test cell was fabricated in the same manner as in Example 4.

[0132] <Comparative Example 2>

[0133] In the preparation of the non-aqueous electrolyte, LiFSI was dissolved at a concentration of 0.5 mol / L and LiPF6 at a concentration of 1.0 mol / L, respectively. Otherwise, the test cell was prepared in the same manner as in Comparative Example 1.

[0134] <Comparative Example 3>

[0135] In the preparation of the non-aqueous electrolyte, LiFSI was not used; LiPF6 was dissolved at a concentration of 1.5 mol / L. Otherwise, the test cell was prepared in the same manner as in Example 2.

[0136] <Comparative Example 4>

[0137] In the preparation of the non-aqueous electrolyte, LiFSI was not used, and LiPF6 was dissolved at a concentration of 1.5 mol / L. Otherwise, the test cell was prepared in the same manner as in Comparative Example 1.

[0138] <Comparative Example 5>

[0139] In the fabrication of the positive electrode, instead of the composite oxide (B1), the following composite oxide (B10) is used. Otherwise, the test cell is fabricated in the same manner as in Example 2.

[0140] [Synthesis of composite oxide (B10)]

[0141] Li₂O and NiO were weighed in a Li:Ni molar ratio of 0.7:1.3, pulverized and mixed to prepare a mixture. The mixture was then calcined at 650°C for 20 hours under an oxygen atmosphere and further crushed to obtain a composite oxide (B₁₀).

[0142] For each test battery cell in the examples and comparative examples, the charge-discharge cycle characteristics were evaluated using the following method. The evaluation results, along with the composition of the positive electrode and non-aqueous electrolyte, are shown in Table 1.

[0143] [Evaluation of Cyclic Performance (Capacity Retention)]

[0144] A test battery cell is subjected to constant-current charging at 0.3C in a temperature environment of 40°C until the battery voltage reaches 4.3V, followed by constant-voltage charging at 4.3V until the current value reaches 0.02C. Thereafter, the battery cell is subjected to constant-current discharging at 0.05C until the battery voltage reaches 2.5V. The charging and discharging are performed for 30 cycles, and the capacity retention rate after 30 cycles is calculated based on the following formula. The capacity retention rate shown in Table 1 is a relative value based on the capacity retention rate of the test battery cell of Comparative Example 4 taken as 100.

[0145] Capacity retention rate=(discharge capacity at the 30th cycle / discharge capacity at the 1st cycle)×100

[0146] [Table 1]

[0147]

[0148] It can be understood from the results shown in Table 1 that compared with the test battery cells of the comparative examples, the test battery cells of the examples all have higher capacity retention rates and excellent cycle characteristics. That is, when using a positive electrode containing a composite oxide (A1) and composite oxides (B1 to B3) represented by the general formula Li a Ni 2-a- b Me b O₂ (wherein 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, and Me is at least one metal element other than Li and Ni) and a non-aqueous electrolyte added with LiFSI, it is found that the cycle characteristics are specifically improved.

[0149] When the composite oxide (A1) is used alone as the positive electrode active material (Comparative Examples 1, 2, 4), when LiFSI is not added to the non-aqueous electrolyte (Comparative Examples 3, 4), and when the composite oxide (B10) that does not satisfy the conditions of the above general formula is used instead of the composite oxides (B1 to B3) (Comparative Example 5), the improvement effect on cycle characteristics as obtained in the examples is not achieved.

[0150] Description of Reference Numerals

[0151] 10: non-aqueous electrolyte secondary battery; 11: positive electrode; 12: negative electrode; 13: separator; 14: electrode assembly; 16: outer can; 17: sealing body; 18, 19: insulating plates; 20: positive electrode lead; 21: negative electrode lead; 22: groove portion; 23: internal terminal plate; 24: lower valve body; 25: insulating member; 26: upper valve body; 27: cover body; 28: gasket; 30: positive electrode core; 31: positive electrode mixture layer; 40: negative electrode core; 41: negative electrode mixture layer; 50: base material; 51: surface layer.

Claims

1. A non-aqueous electrolyte secondary battery, comprising: a positive electrode having a positive electrode layer, a negative electrode, and a non-aqueous electrolyte, wherein, The positive electrode mixture layer contains: General formula Li x Ni 1-y-z Co y M z a first lithium transition metal composite oxide represented by O₂, wherein 0.8≤x≤1.2, 0≤y≤0.2, 0<z≤0.5, and M is at least one element selected from the group consisting of Mn, W, Mg, Mo, Nb, Ti, Si, Al, Zr, B, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, and Ca; and General formula Li a Ni 2-a-b Me b a second lithium transition metal composite oxide represented by O2, wherein 0<a≤0.5, 0≤b≤0.5, and Me is at least one element selected from the group consisting of Cu, Sr, Ca, Nb, Si and Al, The non-aqueous electrolyte contains a sulfonamide salt.

2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The content of the second lithium transition metal composite oxide is 0.1 to 10% by mass relative to the total mass of the positive electrode compound layer.

3. The non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The second lithium transition metal composite oxide is a composite oxide having at least one diffraction peak with a diffraction angle 2θ of 21.40°~21.65° at a light energy of 16keV in synchrotron X-ray diffraction.

4. The non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The sulfonyl imide salt is at least one sulfonyl imide lithium selected from lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

5. The non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The non-aqueous electrolyte contains the sulfonamide salt at a concentration of 0.1 to 1.5 mol / L.

6. The non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, The negative electrode contains a carbon-based active material and a second active material as the negative electrode active material. The second active material is at least one of the following elements and compounds containing the element, wherein the element is selected from at least one of Si, Sn, Sb, Mg and Ge. The content of the second active material is 1 to 15% by mass relative to the total mass of the negative electrode active material.

Citation Information

Patent Citations

  • Internal combustion engine electronic ignition timing controller

    JP1978059140A

  • Cathode material for lithium ion secondary battery and lithium ion secondary battery using it

    US20110129734A1

  • Nonaqueous electrolyte secondary battery

    US20180019500A1

  • Lithium ion secondary battery

    US20190280284A1